Mapping potential forest and land fires around Tumbang Nusa Village area through integration of overlay methods and remote sensing technology - Afitah, Ise; Hatta, Gusti Muhammad; Hafizianor,; Jauhari, Ahmad (Agriculture and Natural Resources, 2024)
Importance of the work: Forest and land fires are disasters that occur every year in Indonesia. One of the areas prone to forest and land fires is the Tumbang Nusa Village area, Central Kalimantan, Indonesia. Objectives: To map the potential for forest and land fires around Tumbang Nusa Village, Central Kalimantan, Indonesia. Materials and Methods: The land fires were mapped around the Tumbang Nusa Village, Central Kalimantan using overlay method and remote sensing technology. Landsat 8 imagery, hotspot data from MODIS and other spatial data were analyzed using the normalized difference vegetation index (NDVI), normalized difference moisture index (NDMI), land surface temperature (LST) and Euclidean distance methods for roads and settlements, as well as overlays. A fire hazard map was produced. Results: Based on the results, variables such as NDVI, NDMI and LST influenced the fire risk in the Tumbang Nusa Village area, Central Kalimantan, Indonesia. However, among these variables, the road access and residential access were the main causes of fire risk in the area. Main finding: The main fire risk was associated with accessibility in the Tumbang Nusa Village area, Central Kalimantan, since access allowed individuals to carry out activities and burn land. Therefore, fire mitigation strategies in the Tumbang Nusa Village area should focus on managing and monitoring accessibility, which should reduce the potential for uncontrolled burning.